2016
DOI: 10.3847/0004-637x/821/2/78
|View full text |Cite
|
Sign up to set email alerts
|

The Optical–infrared Extinction Curve and Its Variation in the Milky Way

Abstract: The dust extinction curve is a critical component of many observational programs and an important diagnostic of the physics of the interstellar medium. Here we present new measurements of the dust extinction curve and its variation toward tens of thousands of stars, a hundred-fold larger sample than in existing detailed studies. We use data from the APOGEE spectroscopic survey in combination with ten-band photometry from Pan-STARRS1, the Two Micron All-Sky Survey, and Wide-field Infrared Survey Explorer. We fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
278
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(312 citation statements)
references
References 76 publications
24
278
5
Order By: Relevance
“…The joint comparison of dust emission and extinction data to other gas tracers will provide additional information on the relation between the total gas and dust, including the abundant dark neutral medium, and will help to better constrain the evolution of dust properties, in particular with regard to potential variations of the extinction curve (Schlafly et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The joint comparison of dust emission and extinction data to other gas tracers will provide additional information on the relation between the total gas and dust, including the abundant dark neutral medium, and will help to better constrain the evolution of dust properties, in particular with regard to potential variations of the extinction curve (Schlafly et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Using E(B-V) to infer N H relies on the assumption that local environment does not change dramatically from sightline to sightline. This is reasonable as the gas-to-dust ratio is relatively constant over a galaxy's disk (Sandstrom et al 2013) and the dust extinction curve only weakly varies across kpc scales (Schlafly et al 2016). Since the metal content of M33's ISM is not yet Table 3.…”
Section: Hydrogen Column Density In Front Of the Starsmentioning
confidence: 95%
“…Outside this layer they are anticorrelated: at high and medium latitudes, less reddening corresponds to larger R V . In an extensive study of the absorption law near the galactic plane, Schlafly, et al (2016), have found a strong correlation between R V and emission in the far IR. This can be explained if the absorption law depends primarily on the size of the dust particles.…”
Section: Three-dimensional Maps Of Extinctionmentioning
confidence: 99%
“…The data of Davenport, et al (2014), are material for further more detailed analysis. Schlafly, et al (2016), have pointed out that in many studies that claim to examine largescale variations in the extinction law at high latitudes, a single narrow range of wavelengths and/or a small number of OB stars have been used, which naturally lie within a narrow layer near the galactic plane; thus, only a few properties of specific stars and media in a negligibly small part of the Galaxy have been analyzed. One example is a much cited (more than 70 times) paper of Fitzpatrick and Massa (2009) that analyzed only 14 OB stars within |Z| < 100 pc.…”
Section: Variations In the Extinction Lawmentioning
confidence: 99%